Coronavirus : the COVID-19 pandemic - Edwards, Sue Bradford (Special reports (Essential Library (Firm)), 2021)
Discusses the origin of COVID-19 in Whuan, China, and explores its spread, diagnosis, and treatment. Also examines efforts to create a vaccine, and the economic, racial, and cultural impact of the virus. Includes color photographs, a glossary, and further resources.